Glorification spells from a priestly milieu in ancient Egypt - Gill, Ann-Katrin 1986-; Smith, Mark 1951- (Oxford University Press, 2024)
"Glorification Spells from a Priestly Milieu in Ancient Egypt presents the first comprehensive edition of an ancient Egyptian ritual composition entitled the Glorification Recited on Each Due Occasion of the Embalming Place, a collection of glorification spells attested in five papyri from around 300 BCE. Arguably the most significant extensive ancient Egyptian ritual text still awaiting systematic study, its constituent spells preserve and transmit religious ideas which resonated with the ancient Egyptians for millennia. The collection and adaptation of these spells into a single coherent ritual work bear witness to the remarkable creativity of the priests and scribes of the latest periods of Egyptian history. Much of this process may be attributable to members of a single family or a small circle of colleagues living in a particular place during a circumscribed period of time, highlighting the importance of individual or small-group agency, not only in preserving and transmitting religious traditions, but in transforming them as well. Glorification spells were recited in the embalming place and elsewhere. They were intended, not only to revivify those to whom they were addressed, restoring their mental and physical faculties, but to secure their elevation to a new, exalted status, that of an akh, or glorified spirit, as well. This status integrated the beneficiary within the hierarchy of gods and other glorified spirits in the next world. This volume places the Glorification Recited on Each Due Occasion of the Embalming Place in its wider historical, religious, and sociological context. It includes a hieroglyphic synopsis of all known examples of the spells, and a transliteration and translation of the copy of them preserved in P. Louvre N. 3129, the type version. [...]"
Keywords: Beschwörung; Totenkult; Ägypten -- Altertum; Quelle